Investigation of future DC distribution network - Qu, Kaiqiang (Nanyang Technological University, 2022)
Due to the worldwide energy shortages and environmental pollution, renewable energy has developed significantly in past 30 years. The development of these renewable power sources has greatly promoted the development of DC power distribution system. In addition, the amount of DC loads and electric vehicles have increased. There are energy losses during power conversions. DC distribution system is expected to overcome the issue. This paper analyses the potential of DC distribution system, it also compares the efficiency difference between AC and DC power distribution system.